Bergerak dalam Diam: Budaya Penguasaan dan Kontestasi Sumber Daya Hutan Lebakbarang - Fahmi Rizki Fahroji (Antropologi Indonesia, 2019)
This article discusses the contestation over forest resources between Perhutani, as an agent of state, and Lebakbarang forest community. The disputes of perspectives and different interests concerning the forest have led to social conflict. The frictions of colonial history and state control over forest in Java also contribute to the long-drawn social conflict. To support the explanation of the forest resources contestation in Lebakbarang, this article presents historical and ethnographic data collected through a fieldwork and literature study. Using Foucault’s approach of governmentality, it tries to understand the forms of Perhutani’s control culture which has implications for the dispute over forest resources in Lebakbarang.